Мовний образ матері в народних піснях і в поезії Тараса Шевченка - Данилюк, Ніна; Danylyuk, Nina (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті розглянуто мовні засоби творення образу Матері в народних піснях і в поезії Тараса Шевченка. Звернуто увагу на особливості його вербалізації в текстах усної словесності, а також на авторське переосмислення Кобзарем. Виділено великий ряд синонімічних одиниць, якими представлено ключове поняття в Шевченкових творах, указано на розширення семантичної структури образних висловів, асоціативно пов’язаних з українською дійсністю та фольклорними традиціями. The article deals with the linguistic means of the creation of image of Mother in the folklore songs and poetic texts by Taras Shevchenko. A special attention has been paid to the peculiar features of its verbalization in the oral texts and to its reconsideration by Kobzar. The row of synonyms that were used to represent this key notion in the works by Shevchenko has been defined: мати, матер, матінка; неня, ненька. The most used dominant word in accordance with A Concordance to the Poetic Works of Taras Shevchenko is мати. It was also pointed out that the semantic structure of the figurative means that have associative connections with the Ukrainian reality and folklore traditions has been broaden. It was noted, that the writer has been used the traditional expressive means and individual author’s artistic attributes, comparisons, metaphors, hyperboles and has been regarded to the Mother like the highest sanctity.
Linguistic Representation of the Image of Mother in the Folklore Songs and Poetry by Taras Shevchenko
Keywords: мовний образ Матері; народнопісенний текст; поетичний текст; мовновиразовий засіб; синонімічний ряд; ключове поняття; семантична структура; a linguistic image of mother; a poetic text; the text of the folklore songs; expressive and representative means; row of synonyms; a key notion; the semantic structure